Effect of Chromium and Aluminium on The Growth of Pleurotus ostreatus - Wee, Ing Kian (2017)
Pollution of metals has concerned as a crucial issue with regards to environmental, human health and industrial biotechnology. Today, various studies were highlighted heavy metals as inducer for production of astaxanthin in Haematococcus pluvialis. However, using light metals to induce the production of astaxanthin in H. pluvialis so far have not been highlighted. In this research, various light metals would be used to induce astaxanthin production in H. pluvialis. The astaxanthin produced in H. pluvialis is then enabling to indicate whether the light metals causing stress and toxicity towards the H. pluvialis. In this research, Al, Li and Mg with different concentrations were chosen to induce the astaxanthin production in H. pluvialis. In the other word, there was also focus on the effect of light metals with different pH toward the astaxanthin production in H. pluvialis. Al, Li & Mg with different pH and concentrations were exposed to H. pluvialis cells. In this case, the astaxanthin production was measured using spectrophotometric methods by exposure to light metals with several durations. After study the topic, the effect of light metals with different pH and concentrations toward astaxanthin production in H. pluvialis would indirectly shows that whether astaxanthin considered as a sensitive indicator for light metals. The astaxanthin production from H. pluvialis cells able to be measuring by detection of absorbance using light spectrophotometer at 482 nm. From the research, the Mg shows highest percentage of astaxanthin production if compared to Al and Li. This had indicated that there were different oxidative stresses conducted by different light metals. Besides that, pH 7 of Al solution also shows the highest percentage of astaxanthin production when compared to other pH values. This also indicated that different pH causes a different level of oxidative stress towards H. pluvialis. As a summary, astaxanthin was proven as a sensitive indicator for light metals with different pH and concentrations. It also has ability to differentiate the different level oxidative stresses causing by different type of light metals.